2020
DOI: 10.3390/md18090452
|View full text |Cite
|
Sign up to set email alerts
|

New Biscembranoids Sardigitolides A–D and Known Cembranoid-Related Compounds from Sarcophyton digitatum: Isolation, Structure Elucidation, and Bioactivities

Abstract: Chemical examination from the cultured soft coral Sarcophyton digitatum resulted in the isolation and structural identification of four new biscembranoidal metabolites, sardigitolides A–D (1–4), along with three previously isolated biscembranoids, sarcophytolide L (5), glaucumolide A (6), glaucumolide B (7), and two known cembranoids (8 and 9). The chemical structures of all isolates were elucidated on the basis of 1D and 2D NMR spectroscopic analyses. Additionally, in order to discover bioactivity of marine n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Cell lines were purchased from the American Type Culture Collection (Rockville, MD, USA). Cytotoxicity testing for all compounds 1 – 14 was carried out using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay as in the previous report [ 31 , 32 ]. Doxorubicin, the positive control in the MTT assay, showed cytotoxicity towards MCF-7, MDA-MB-231, HepG2, and HeLa cancer cell lines, with IC 50 values of 6.8 ± 1.4, 6.3 ± 1.2, 9.6 ± 1.8, and 8.1 ± 2.1 ( µ M), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell lines were purchased from the American Type Culture Collection (Rockville, MD, USA). Cytotoxicity testing for all compounds 1 – 14 was carried out using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay as in the previous report [ 31 , 32 ]. Doxorubicin, the positive control in the MTT assay, showed cytotoxicity towards MCF-7, MDA-MB-231, HepG2, and HeLa cancer cell lines, with IC 50 values of 6.8 ± 1.4, 6.3 ± 1.2, 9.6 ± 1.8, and 8.1 ± 2.1 ( µ M), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Murine macrophage cell line J774A.1 was purchased from the American Type Culture Collection. Screening about the generation of pro-inflammatory cytokines in LPS-stimulated J774A.1 macrophage cells was carried out according to the previous report [ 32 ]. The concentrations of the produced cytokines were measured using ELISA according to the previous work [ 33 ] and manufacturer′s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The only known cembranoid collected from this species namely isosarcophytonolide D 147 . The reported cembrane-type diterpenoid from S. digitatum was reported to display various anti-cancer and anti-inflammatory activities [ 45 ]. Another study reported nine cembranoids from Sarcophyton tenuispiculatum which culture at Kaohsiung Medical University, Taiwan.…”
Section: Cembranoidsmentioning
confidence: 99%
“…In addition, 146 exhibited cytotoxicity towards MCF-7, MDA-MB-231, and HepG2 with IC 50 value of 9.4 ± 3.0; 17.8 ± 4.5; 14.9 ± 4.2 µg/mL, respectively. Lastly, 147 showed cytotoxicity towards MCF-7 with an IC 50 value of 10.9 ± 4.3 µg/mL [ 45 ].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…These secondary metabolites help the organisms to defend themselves against the predators and adapt to the environment stress [ 5 ]. Furthermore, some of the isolates have been demonstrated to possess various biological activities, such as cytotoxic [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], anti-inflammatory [ 6 , 7 , 13 , 14 , 15 , 16 , 17 , 18 ], neuroprotective [ 19 ], antibacterial [ 19 ], and antiviral activities [ 12 , 20 ]. The diversified structures and various biological applications of marine natural products thus prompt us to further explore the secondary metabolites from organisms of the Sarcophyton genus.…”
Section: Introductionmentioning
confidence: 99%